Design and Construction of Automatic Fish Feeder using Atmel 8052 Microcontroller - KO Ojo; OA Benard (Journal of Applied Sciences and Environmental Management)
This paper was proposed to design an automatic fish feeder system using Atmel microcontroller application. In a way, it is to control the fish feeding activity by using a fish feeder that combined the mechanical and electrical system to form a device which control the fish feeding activity. This device consists of feed storage, feed stand, display unit, microcontroller and DC motor. The feeds controlled by DC motor which is located under feed storage. A control system was then attached to this device allowing the fish to be fed at preset time as required by user. Hence, promising efficiency and productivity in fish pond in long run. Display unit his is basically the user interface where working of the system is displayed on a screen so that the user have an idea what is going on the system. The message will be displayed on a 16 by 2 liquid crystal display. The controller came with a keypad giving users more option in determining the suitable speed for the motor. In addition, the feed in the automatic fish feeder system will be controlled by the rotation speed of DC motor. Test results at the discharge interval of 4hours and dispensing time of 90minutes within 24hours showed that 15kg of feeds were evenly broadcast across the pond of 12cm less amount of feed lost was recorded compare to manual feeding. The machine adequately manages and preserves feed under harsh conditions.